(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
This article discusses the role of syntactic analysis in ensuring grammatical accuracy. In particular, structural analysis methods developed by scientists and theories based on them are analyzed for syntactic analysis (parsing), which can automatically analyze certain syntactic units and structures in the text. The main goal of this article is to clarify the tasks of structural analysis methods in the syntactic analysis of sentences, and the common and different aspects of various grammatical theories created based on the characteristics of languages are highlighted.